Diversity of medicinal plant uses and epidemiological analysis during the COVID-19 pandemic in Biskra (south-eastern of Algeria) - Dehimat, Abdelouahab; Hemidi, Khaoula; Segueni, Narimane; Bendif, Hamdi (Biodiversity: Research and Conservation, 2025)
In this study we examined data on COVID-19 patients recorded in 2020 at the Hakim Sadanne Hospital in the Biskra, Algeria and applied various tests: statistical, epidemiological, etc. In addition, we conducted interviews with herbalists and an ethnobotanical on-line survey of medicinal plants used during the COVID-19 pandemic. A total of 2108 cases of this disease, including 931 deaths, were analysed to link various factors, such as air temperature, age, and sex, with mortality rate. Our results demonstrate that the appearance of symptoms of infection was often associated with pre-existing chronic diseases, particularly diabetes, cardiovascular heart disease, and high blood pressure. As for medicinal plants, Melissa officinalis and Zingiber officinale were the most used during the pandemic, whereas Eucalyptus globulus and Syzygium aromaticum had 100% fidelity levels. In conclusion, primarily the above-mentioned chronic diseases were associated with reduced immunity to COVID-19. Furthermore, traditional medicine has been an accommodating alternative to conventional medical treatment of COVID-19 within Biskra region.